P70 Investigating the current state of practice for reporting on surgeon's learning and the learning curve in IDEAL studies of surgical innovation: A systematic review. (8th April 2021) - Shah, Max; Alford, Natasha; Mutanga, Ian; Hudson, Elizabeth; Shah, Maximilian
Abstract: Introduction: Community learning is a key component for the progression of surgical innovation, which is itself crucial to advancing surgical practice. Assessment of learning curve's (LCs) allow rigorous evaluation of new surgical procedures/devices and their introduction into clinical practice. The Idea–Development–Exploration–Assessment–Long-term (IDEAL) framework provides recommendations for the evaluation of new surgical procedures and devices throughout the stages of innovation. This study aimed to identify the current reporting practice of LCs in IDEAL studies. Methods: A systematic review was conducted to identify author-reported IDEAL/IDEAL-D studies of any IDEAL stage and surgical specialty. Included were primary studies citing any of 10 key IDEAL papers. Data were extracted including information relating to surgeons' experience and training, support and performance monitoring, and methods for measuring and assessing the LC. Results: Searches yielded 1411 publications, of which 59 studies met the eligibility criteria. Some 31/59 (53%) studies reported information on the LC, however, only 3 (5%) studies measured or reported on LC in detail. These 3 papers included statistical methods (cumulative sum control charts, Shewhart control charts and multivariate analysis). Some 21/59 (36%) studies reported training for surgeons and 16 (27%) reported support or performance monitoring. Conclusion: Reporting of the LC or factors influencing LC such as training, was found to be poor in the included studies. Development of more detailed guidance for measuring and reporting the LC in future studies is recommended to facilitate robust evaluation of new surgical procedures and devices.